A Review of Recent Advances in 3D Bioprinting With an Eye on Future Regenerative Therapies in Veterinary Medicine - Jamieson, Colin; Keenan, Patrick; Kirkwood, D'Arcy; Oji, Saba; Webster, Caroline; Russell, Keith A.; Koch, Thomas G. (Frontiers in Veterinary Science, 2021)
3D bioprinting is a rapidly evolving industry that has been utilized for a variety of biomedical applications. It differs from traditional 3D printing in that it utilizes bioinks comprised of cells and other biomaterials to allow for the generation of complex functional tissues. Bioprinting involves computational modelling, bioink preparation, bioink deposition, and subsequent maturation of printed products; it is an intricate process where bioink composition, bioprinting approach, and bioprinter type must be considered during construct development. This technology has already found success in human studies, where a variety of functional tissues have been generated for both in vitro and in vivo applications. Although the main driving force behind innovation in 3D bioprinting has been utility in human medicine, recent efforts investigating its veterinary application have begun to emerge. To date, 3D bioprinting has been utilized to create bone, cardiovascular, cartilage, corneal and neural constructs in animal species. Furthermore, the use of animal-derived cells and various animal models in human research have provided additional information regarding its capacity for veterinary translation. While these studies have produced some promising results, technological limitations as well as ethical and regulatory challenges have impeded clinical acceptance. This article reviews the current understanding of 3D bioprinting technology and its recent advancements with a focus on recent successes and future translation in veterinary medicine.